Resource-Based View and Dynamic Capability with Contextual Factors for Organizational Survival - Daniel Ong; Yohana F. Cahya Palupi (Jurnal Ilmiah Manajemen Kesatuan, 2026)
This study is motivated by the increasing environmental turbulence and uncertainty that have contributed to the declining lifespan of firms and the growing need for organizational survival capabilities. The aim of this research is to integrate the Resource-Based View (RBV) and Dynamic Capabilities (DC) perspectives to provide a more comprehensive explanation of organizational survival. The study employs a qualitative design using an interpretive meta-synthesis approach of 80 selected scholarly sources, analyzed through thematic analysis and meta-ethnography techniques. The findings reveal that organizational survival is determined by the configuration of tangible and intangible resources, dynamic capabilities in sensing, seizing, and transforming, and the synergistic integration of RBV and DC through processes of resource orchestration, bundling, and reconfiguration. In addition, contextual factors such as industry dynamics, institutional environments, and culture significantly influence survival strategies. The study implies that managers need to balance resource exploitation with adaptive flexibility by strengthening resource orchestration, dynamic capabilities, and contextual sensitivity to sustain long-term competitive advantage. In conclusion, organizational survival is the outcome of the integrated interaction between RBV, DC, and external contextual factors that jointly shape sustained organizational competitiveness in turbulent and uncertain environments.